2021
DOI: 10.1093/rapstu/raaa022
|View full text |Cite
|
Sign up to set email alerts
|

The Night and Day of Amihud’s (2002) Liquidity Measure

Abstract: The version presented here is a Working Paper (or 'pre-print') that may be later published elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Evidently, this duality posits a challenge to current liquidity measures. More recently, Barardehi et al (2021) highlighted the importance of excluding information-driven price movements when constructing measures of stock liquidity and achieved improvements in Amihud's ALR by replacing close-to-close with open-to-close returns and excluding off-hours trades, which create noise in ALR.…”
Section: Discussion and Recent Developmentsmentioning
confidence: 99%
“…Evidently, this duality posits a challenge to current liquidity measures. More recently, Barardehi et al (2021) highlighted the importance of excluding information-driven price movements when constructing measures of stock liquidity and achieved improvements in Amihud's ALR by replacing close-to-close with open-to-close returns and excluding off-hours trades, which create noise in ALR.…”
Section: Discussion and Recent Developmentsmentioning
confidence: 99%
“…The original Amihud illiquidity measure is calculated on a daily basis, comparing close to the previous day close to calculate the absolute return compared to the volume in USD. It is not necessary to apply revision due to the case of a trade-by-trade basis, as open price and prior-close price are coincident (Barardehi et al 2020). The mean of the daily data of each stock is used as input for the constituents of the quartile-period panel.…”
Section: Methodsmentioning
confidence: 99%
“…This restriction leads to a discount on daily opening prices, thus inducing negative overnight returns. In recent years, literature on the components of return, that is, intraday return and overnight return, is widely studied by scholars (Aboody et al, 2018;Lou et al, 2019;Barardehi et al, 2021). Aboody et al (2018) demonstrate that individual stock overnight returns possess the same characteristics as the investor sentiment; thus, we can use the stock overnight return as the proxy of the investor sentiment at the stock level.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lou et al (2019) confirmed that different types of agents tend to trade at different times during the day, that is, some investors may tend to trade at the morning open, while others may prefer to trade during the rest of the day up to and including the market close, which makes the price movement during the day and at night vary. Also, Boudoukh et al (2019) and Barardehi et al (2021) argued that overnight price movements are mainly due to public news, as opposed to the revelation of private information through trading. Consequently, in this study, based on the investor structure, T+1 trading rules, and price movements at night vs. during the day, we empirically analyze the cross-sectional relation between ESG and expected overnight and intraday components of returns in the Chinese stock market.…”
Section: Introductionmentioning
confidence: 99%